Dominant RDH12-retinitis pigmentosa impairs photoreceptor development and implicates cone involvement in retinal organoids - Cécile Méjécase; Cécile Méjécase; Ya Zhou; Nicholas Owen; Pablo Soro-Barrio; Riccardo Cheloni; Riccardo Cheloni; Neelima Nair; Hajrah Sarkar; Hajrah Sarkar; Lyes Toualbi; Lyes Toualbi; et al. (Frontiers in Cell and Developmental Biology)
IntroductionRetinal dehydrogenase 12 (RDH12) is a photoreceptor NADPH-dependent retinal reductase enzyme, converting all-trans-retinal to all-trans-retinol. Heterozygous variants in RDH12 cause a rare autosomal dominant (AD) retinitis pigmentosa.MethodsAs no disease models exist, we generated human induced pluripotent stem cell-derived retinal organoids (RO) from an RDH12-AD patient (with pathogenic variant c.759del, p.Phe254Leufs*24) alongside a healthy, unaffected control.ResultsRDH12-AD RO exhibited correct localization of RDH12 to the photoreceptor inner segments up to week 44; however, transmission electron microscopy at week 37 showed that photoreceptors were less abundant and shorter in length. Visual cone function, retinol biosynthesis, and the vitamin A pathway were also highly disrupted at week 44.DiscussionOur study is the first to describe an RDH12-AD disease model with pathology at later stages of photoreceptor differentiation, in keeping with the milder disease course seen in humans. It provides insights into the etiology and possible targets for future therapeutic development.